HEAVY METAL CONCENTRATIONS IN THE WATER AND FISH MUSCLES OF LAKES OGELUBE AND OJII IN SOUTHEASTERN NIGERIA - Onah, Ikechukwu (Polish Journal of Natural Sciences, 2023)
Heavy metal pollution is one of the major environmental challenges facing aquatic ecosystem. Heavy metal pollution of lakes and subsequent accumulation in the tissues of fish inhabiting the lakes could impair the use of the lake water and constitute a public health hazard to consumers of fish from the lake. We investigated the concentration of Chromium (Cr), Copper (Cu), Iron (Fe), Lead (Pb) and Zinc (Zn) in water and fish muscles in Ogelube and Ojii lakes, southeastern Nigeria using Atomic Absorption Spectrometer (AAS). All the heavy metals studied were detected in both lakes. The concentrations of all the heavy metals were higher in Ojii lake than Ogelube lake except for Cu and Zn which had equal concentrations in the two lakes. There was no significant difference in the concentration of the heavy metals between the two lakes. Pb was not detected in the fish muscle in both lakes. In Ogelebu lake, the concentration of Fe was significantly higher in Hepsetus odoe than Coptodon zillii (P<0.05). In Ojii lake, the concentration of Cr was significantly higher in C. zillii than H. odoe while the concentration of Fe was significantly higher in H. odoe than C. zillii (P<0.05). The concentrations of the studied heavy metals in the lake water exceeded the acceptable limits permissible by WHO except Cu which is below the acceptable limit. The heavy metal concentrations in the fishes were within the safe levels for human consumption.